2007
DOI: 10.1097/01.mlr.0000237425.58554.66
|View full text |Cite
|
Sign up to set email alerts
|

The Complexity of Care for Patients with Rheumatoid Arthritis

Abstract: Patients with RA have frequent encounters with multiple providers and also frequent discontinuity of care. Recognizing the complexity of the care of patients with a chronic disease across multiple dimensions provides an opportunity to better understand challenges and opportunities in delivering high quality care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…CVD studies were predominantly from European countries, with several also from the US & Asia. For the MSD spectrum, six mean PCS estimates for LBP [ 4 , 10 , 31 , 40 42 ], seven for OA [ 3 , 10 , 31 , 33 , 41 , 43 ] and four for RA [ 25 , 44 – 46 ] were identified. MSD studies were predominantly from European countries, with several also from the US.…”
Section: Resultsmentioning
confidence: 99%
“…CVD studies were predominantly from European countries, with several also from the US & Asia. For the MSD spectrum, six mean PCS estimates for LBP [ 4 , 10 , 31 , 40 42 ], seven for OA [ 3 , 10 , 31 , 33 , 41 , 43 ] and four for RA [ 25 , 44 – 46 ] were identified. MSD studies were predominantly from European countries, with several also from the US.…”
Section: Resultsmentioning
confidence: 99%
“…This cross‐sectional study queried physicians identified as fulfilling key roles by a population‐based sample of breast cancer patients in the Los Angeles Women's Health Study (LAW) (Chen et al 2008; Yoon et al 2008a, b) regarding the structure and organization of breast cancer care (Tisnado et al 2009). Physicians were considered as fulfilling key roles if they were named by a patient as specifically performing a cancer‐related function such as being the doctor in charge of decision making for delivery of chemotherapy, radiation therapy, or surgery (Kahn et al 2007). The sampling strategy is explained in greater detail in Appendix SA2.…”
Section: Datamentioning
confidence: 99%
“…2 Patients with RA have an average of 6 visits per year with rheumatologists, in comparison with 5 visits in primary care (PC), underscoring the need for timely PC follow-up of elevated BP to diagnose and treat hypertension. 3 The American College of Rheumatology recognizes the need for BP control and has endorsed timely follow-up of elevated BPs as a quality measure for the Merit-based Incentive Payment System, defined as ≤4 weeks. 4 In prior work, our multidisciplinary team adapted a PC hypertension protocol and developed an implementation plan geared at rheumatology and specialty clinics.…”
mentioning
confidence: 99%
“…We previously reported that only 10% of eligible RA visits recommended follow-up of high blood pressure (BP) and that RA patients were less likely to have their hypertension diagnosed despite meeting identical longitudinal BP thresholds as peers 2 . Patients with RA have an average of 6 visits per year with rheumatologists, in comparison with 5 visits in primary care (PC), underscoring the need for timely PC follow-up of elevated BP to diagnose and treat hypertension 3 . The American College of Rheumatology recognizes the need for BP control and has endorsed timely follow-up of elevated BPs as a quality measure for the Merit-based Incentive Payment System, defined as ≤4 weeks 4…”
mentioning
confidence: 99%